Dietary quality and adequacy among Aboriginal alcohol consumers in the Northwest Territories, Canada - Rittmueller, Stacey E. (Co-Action Publishing, 2012)
OBJECTIVES: The present study aimed to assess dietary adequacy and quality among Inuvialuit alcohol consumers and non-consumers in the Northwest Territories (NWT), Canada. STUDY DESIGN: Cross-sectional study. METHODS: A validated quantitative food frequency questionnaire was administered to individuals (n =216) of randomly selected households in 3 NWT communities to capture dietary intake and alcohol consumption over a 30-day recall period. The daily energy and nutrient intake, dietary adequacy and the top food sources of energy and selected nutrients were determined by alcohol consumption status. RESULTS: Energy intake was higher among all alcohol consumers regardless of gender. Male alcohol consumers had lower nutrient intake density (per 4,184 kJ) of protein, cholesterol and several micronutrients (p≤0.05), and female alcohol consumers had lower intake density of saturated fat (p≤0.01), thiamine, folate and sodium (p≤0.05). Among all men and women, 70–100% had inadequate intakes of dietary fibre, vitamin E and potassium. Non-nutrient-dense foods contributed similar amounts and traditional foods (TF) contributed 3% less to energy comparing alcohol consumers to non-consumers. CONCLUSION: Nutrient inadequacies are prevalent among Aboriginal populations in the Canadian Arctic and may be exacerbated by alcohol consumption due to alcohol's effects on dietary intake, nutrient transport and metabolism. Adult Inuvialuit who consumed alcohol had increased caloric intake and consumed similar amounts of non-nutrient-dense foods and less nutrient-dense TF. Fewer dietary inadequacies were observed among alcohol consumers than non-consumers, which might be due to the increase in overall food intake among alcohol consumers; however, further exploration of volume and pattern of drinking might help explain this result.